2013
DOI: 10.1111/nyas.12145
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenic effects of resveratrol in vitro: potential for the prevention and treatment of osteoporosis

Abstract: There are a number of pharmacological agents for the treatment of bone mineral loss and osteoporosis. Hormone replacement therapy (HRT) with estrogen is an established treatment, but it has several adverse side effects and can increase the risk of cancer, heart disease, and stroke. There is increasing interest in nutritional factors and naturally occurring phytochemical compounds with the potential for preventing age-related and postmenopausal bone loss. Resveratrol (3,5,4'-trihydroxy-trans-stilbene) is a poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
41
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(49 citation statements)
references
References 46 publications
5
41
0
3
Order By: Relevance
“…To testify our hypothesis, we did in vitro study with BMSCs, which were potential for osteoblast differentiation. Resveratrol has been reported to play a positive role in osteoblast differentiation of BMSCs and adipose derived stromal cells [11,23]. Our study further verified that resveratrol could promote osteoblast differentiation of BMSCs.…”
Section: Discussionsupporting
confidence: 74%
“…To testify our hypothesis, we did in vitro study with BMSCs, which were potential for osteoblast differentiation. Resveratrol has been reported to play a positive role in osteoblast differentiation of BMSCs and adipose derived stromal cells [11,23]. Our study further verified that resveratrol could promote osteoblast differentiation of BMSCs.…”
Section: Discussionsupporting
confidence: 74%
“…Studies in the past have found that HRT has a protective effect on BMD (19,31,36). Similarly, in our study, postmenopausal women who received HRT were less likely to have osteoporosis.…”
Section: Discussionsupporting
confidence: 61%
“…Fermentation of anthocyanins may enhance their intestinal absorption and bioactivities by removing glycosides. No previous studies have investigated the alleviation of postmenopausal symptoms by anthocyanin-rich foods fermented with L. plantarum and A. oryzae, although resveratrol, a bioactive compound of wine (the alcohol fermentation of anthocyanin-rich foods) has been studied (Mobasheri and Shakibaei 2013;Nguyen et al 2012). The present study revealed that fermenting the extracts of black carrots with L. plantarum and A. oryzae changed the anthocyanin composition by increasing anthocyanin aglycones (-cyanidin and malvidin) and the changes in composition improved their effectiveness for improving energy homeostasis with BCAO being the most effective for increasing daily energy expenditure and fat oxidation.…”
Section: Discussionmentioning
confidence: 99%